O problema da representação do outro em O moleque Ricardo, de José Lins do Rego - Giseli Ferreira Barros (2017)
This dissertation aims analyzing the novel O moleque Ricardo, in order to identify and comprehend how the characters of the migrant and the proletariat (the other), so far absent from the universe of the author, centered in the rural environment of the mill, are represented and built in this narrative. To do so, the study of the novel focuses on analyzing theconstruction of the main character and his relationship with supporting characters, the construction of the narrative, as well as this novel and the use of its language, aiming the technical resolution of the problem through the introduction of new social types in the fictional universe of the author. This project also intends the investigation of the use ofimages in the romance in scenes that are highlighted in the narrative, giving them an internal power which boosts and legitimizes them literarily.